Extensive giant cell tumor on the foot completely wrapping the extensor hallucis longus: case report - Gomes, Anderson Humberto; Pádua, Bruno Janotti; Teixeira, Luiz Eduardo Moreira; Gonçalves Soares, Claudio Beling (Scientific Journal of the Foot & Ankle, 2018)
In this study, we report the case of a patient with a lobulated expansile lesion of 16.6 cm in its largest diameter, who was referred as having a simple “synovial cyst” in the foot that actually was a giant cell tumor of the tendon sheath along the extensor hallucis longus. Conducting a differential diagnosis of a “synovial cyst” in the foot and ankle, performing adequate surgical planning and using imaging tests, such as nuclear magnetic resonance, increases the probability of treatment success. Level of Evidence V; Therapeutic Studies; Expert Opinion.